Ski Touring and Snowshoeing in the Hautes–Bauges (Savoie, France): a Study of Various Sports Practices and Ways of Experiencing Nature - Clémence Perrin-Malterre; Laine Chanteloup (Revue de Géographie Alpine)
This article deals with winter outdoor recreation and the use of mountain wilderness areas in the Hautes-Bauges massif. The study aims to define outdoor recreation profiles of users of the areas according to socio-demographic data, recreational practices, and perceptions of the wilderness environment. The results show four (4) different recreation profiles. For all of them bonding with the natural environment is really important. Most users want to conserve and protect the wilderness areas. Nevertheless, this majority also claims the right to have access to this natural environment preferring above all that it remains a place for recreation. Thus, even if the natural setting of the mountains is the main component of their outdoor activities, these elements are mainly apprehended to the prism of their bodily experience.